Influence of Endometriosis on Assisted Reproductive Technology Outcomes: A Systematic Review and Meta-analysis. Issue 1 (January 2015) - Hamdan, Mukhri; Omar, Siti Z.; Dunselman, Gerard; Cheong, Ying
Abstract : OBJECTIVE: To investigate the association of endometriosis on assisted reproductive technology (ART) outcomes and to review if surgical treatment of endometriosis before ART affects the outcomes. DATA SOURCES: We searched studies published between 1980 and 2014 on endometriosis and ART outcome. We searched MEDLINE, PubMed, ClinicalTrials.gov, and Cochrane databases and performed a manual search. METHODS OF STUDY SELECTION: A total of 1, 346 articles were identified, and 36 studies were eligible to be included for data synthesis. We included published cohort studies and randomized controlled trials. TABULATION, INTEGRATION, AND RESULTS: Compared with women without endometriosis, women with endometriosis undertaking in vitro fertilization and intracytoplasmic sperm injection have a similar live birth rate per woman (odds ratio [OR] 0.94, 95% confidence interval [CI] 0.84–1.06, 13 studies, 12, 682 patients, I 2 =35%), a lower clinical pregnancy rate per woman (OR 0.78, 95% CI 0.65–0.94), 24 studies, 20, 757 patients, I 2 =66%), a lower mean number of oocyte retrieved per cycle (mean difference −1.98, 95% CI −2.87 to −1.09, 17 studies, 17, 593 cycles, I 2 =97%), and a similar miscarriage rate per woman (OR 1.26, 95% CI (0.92–1.70, nine studies, 1, 259 patients, I 2 =0%). Women with more severe disease (American Society for Reproductive Medicine III–IV) have a lower live birth rate, clinical pregnancy rate, and mean number of oocytes retrieved when compared with women with no endometriosis. CONCLUSION: Women with and without endometriosis have comparable ART outcomes in terms of live births, whereas those with severe endometriosis have inferior outcomes. There is insufficient evidence to recommend surgery routinely before undergoing ART. Abstract : Women with and without endometriosis have comparable assisted reproductive technology outcomes in terms of live births, whereas those with severe endometriosis have inferior outcomes.